2022
DOI: 10.1186/s12935-022-02564-4
|View full text |Cite
|
Sign up to set email alerts
|

Cell type-specific response of colon cancer tumor cell lines to oncolytic HSV-1 virotherapy in hypoxia

Abstract: Background Novel strategies are required since the hypoxic tumor microenvironment is one of the important impediments for conventional cancer therapy. High mobility group box 1 (HMGB1) protein can block aerobic respiration in cancer cells. We hypothesized that HMGB1could also kill the colorectal cancer cells during hypoxia. Methods In this study, we developed oncolytic herpes simplex virus type 1 expressing HMGB1 protein (HSV-HMGB1) and investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 55 publications
(62 reference statements)
0
12
0
Order By: Relevance
“… 8 On the other hand, overexpression of HMGB1 by an oHSV was shown to mildly increase the cytotoxicity of oHSV in hypoxic colon cancer cells in vitro . 29 To specifically delineate the impact of secreted HMGB1 on virus replication, we utilized an HMGB1-blocking antibody. Although blockade of secreted HMGB1 did not affect virus replication in vitro , we observed that mice treated with an HMGB1-blocking antibody lived longer, primarily due to reduced edema in vivo .…”
Section: Discussionmentioning
confidence: 99%
“… 8 On the other hand, overexpression of HMGB1 by an oHSV was shown to mildly increase the cytotoxicity of oHSV in hypoxic colon cancer cells in vitro . 29 To specifically delineate the impact of secreted HMGB1 on virus replication, we utilized an HMGB1-blocking antibody. Although blockade of secreted HMGB1 did not affect virus replication in vitro , we observed that mice treated with an HMGB1-blocking antibody lived longer, primarily due to reduced edema in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia is common in majority of malignant tumors and an attractive therapeutic target. As hypoxia targeted treatment are effective in patients with the most hypoxic tumors, hypoxic signature might be useful for developing proper treatment, such as engineered oncolytic viruses that could be utilized to control or regulate the biological interactions responsible for the functioning or malfunctioning of cancer cells during hypoxia [ 22 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Cells were seeded in a T25 flask and cultured in DMEM medium supplemented with 10% FBS. The cells were repeatedly incubated in hypoxic conditions in an Anoxomat chamber (Mart Microbiology, Lichtenvoorde, The Netherland; 1% O 2 ) for 4 h and then incubated in a standard culture environment (5% CO 2 and 95% air) at 37 °C for 48-72 h. Cells were treated twice weekly, and hypoxic-conditioned cell lines were generated after 20 exposures to hypoxia [ 22 ] .…”
Section: Methodsmentioning
confidence: 99%
“…Hypoxia is a constant in the TME, which is attributed to the inefficient tumor vascular system's poor oxygenation (Jing et al, 2019). The cytotoxicity of an HSV-1 (HSV-HMGB1) expressing the HMGB1 protein, which inhibits tumor cell aerobic respiration, was tested in both normoxic and hypoxic conditions against three colorectal cancer cell lines (HCT116, SW480, and HT29) and compared to the parental virus HSV-ble (Shayan et al, 2022). In both states, HSV-HMGB1 was significantly more virulent than its parental virus for HCT116 and SW480.…”
Section: Colorectal Cancermentioning
confidence: 99%